A Blueprint for maximizing the social and economic value of aviation (IATA Washington, D.C.US, 2016)
Provides guidelines on how to achieve a robust platform for growth in the aviation industry in the Caribbean, explains why this is desirable, supported by figures and analysis.
Keywords: AIR TRANSPORT